2010
DOI: 10.1074/jbc.m110.180646
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of Cytochrome P450 2B4 as Investigated by Hydrogen-Deuterium Exchange Mass Spectrometry and X-ray Crystallography

Abstract: Crystal structures of the xenobiotic metabolizing cytochrome P450 2B4 have demonstrated markedly different conformations in the presence of imidazole inhibitors or in the absence of ligand. However, knowledge of the plasticity of the enzyme in solution has remained scant. Thus, hydrogen-deuterium exchange mass spectrometry (DXMS) was utilized to probe the conformations of ligand-free P450 2B4 and the complex with 4-(4-chlorophenyl)imidazole (4-CPI) or 1-biphenyl-4-methyl-1H-imidazole (1-PBI). The results of DX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 52 publications
(85 citation statements)
references
References 77 publications
9
75
1
Order By: Relevance
“…These include two distinct ligand-free states of protein, open and closed, as well as other conformations observed in complex with various inhibitors and drugs (Gay et al, 2010a). The crystal structures of the open ligand free form and two inhibitor-bound complexes were in agreement with the conformational changes observed in solution in recent hydrogen-deuterium exchange mass spectrometry experiments (Wilderman et al, 2010). Furthermore, the flexible regions of 2B4 affected by ligand binding were consistent between the solution studies and X-ray crystal structures.…”
Section: Introductionsupporting
confidence: 74%
“…These include two distinct ligand-free states of protein, open and closed, as well as other conformations observed in complex with various inhibitors and drugs (Gay et al, 2010a). The crystal structures of the open ligand free form and two inhibitor-bound complexes were in agreement with the conformational changes observed in solution in recent hydrogen-deuterium exchange mass spectrometry experiments (Wilderman et al, 2010). Furthermore, the flexible regions of 2B4 affected by ligand binding were consistent between the solution studies and X-ray crystal structures.…”
Section: Introductionsupporting
confidence: 74%
“…This new ligand-free structure (Fig. 1C) (Wilderman et al, 2010) differed significantly from the previously reported open ligand-free structure (Fig. 1B) (Scott et al, 2003), showing that CYP2B4 is able to adopt a closed conformation in the absence of ligand that closely resembles the 4-CPI and 1-CPI complexes.…”
Section: Introductioncontrasting
confidence: 65%
“…1B) (Scott et al, 2003), showing that CYP2B4 is able to adopt a closed conformation in the absence of ligand that closely resembles the 4-CPI and 1-CPI complexes. Whereas the backbone maintains an RMSD of Ͻ0.8 Å compared with the other CYP2B4 closed structures, the active site cavity is intermediate to the smaller volume of the 4-CPI active site and the larger volume of the 1-CPI active site (Gay et al, 2010a;Wilderman et al, 2010). This change in volume is mostly due to the movement of Glu301 out of the active site (Fig.…”
Section: Introductionmentioning
confidence: 93%
“…Solubilization and crystallization of the former group of MPs also require the use of detergents to sequester hydrophobic protein patches and prevent protein aggregation. By mixing them with commercial detergents, FAs have been successfully used to crystallize several mammalian P450 enzymes [CYP24A1 (27), CYP2B4 (28)(29)(30)(31)(32), and CYP2B6 (32)(33)(34)]. Here, we provide a summary of these results (Table S4).…”
Section: Significancementioning
confidence: 97%